2020
DOI: 10.21037/tcr.2019.12.03
|View full text |Cite
|
Sign up to set email alerts
|

Plumbagin inhibits tumor angiogenesis of gastric carcinoma in mice by modulating nuclear factor-kappa B pathway

Abstract: Background: We aimed to determine the mechanism of plumbagin on tumor growth of gastric carcinoma.Methods: Sixty BALB/c mice were treated with 200 µL SGC-7901 cells to establish gastric carcinoma xenograft and randomly divided into four groups: model group, low dose of plumbagin group (2 mg/kg), medium dose of plumbagin group (4 mg/kg) and high dose of plumbagin group (6 mg/kg). The tumor volume and weight were measured every week, and the ratio of anti-tumor was analyzed. The contents of vascular endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…Because of the heterogeneity and plasticity of macrophages, their phenotype and function are regulated by the surrounding microenvironment. It has been shown that GC‐exo induce the M2 phenotype differentiation of macrophages by activating the NF‐κB pathway 38 . In addition, GC‐exo can polarize monocytes into PD‐1 + ‐tumor‐associated macrophages with an immunosuppressive phenotype and function to promote GC progression 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the heterogeneity and plasticity of macrophages, their phenotype and function are regulated by the surrounding microenvironment. It has been shown that GC‐exo induce the M2 phenotype differentiation of macrophages by activating the NF‐κB pathway 38 . In addition, GC‐exo can polarize monocytes into PD‐1 + ‐tumor‐associated macrophages with an immunosuppressive phenotype and function to promote GC progression 21 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that GCexo induce the M2 phenotype differentiation of macrophages by activating the NF-κB pathway. 38 In addition, GCexo can polarize monocytes into PD-1 + -tumor-associated macrophages with an immunosuppressive phenotype and function to promote GC progression. 21 In the present study, we found MFC-exo induced the lung macrophage expression of PD-L1 and led to pulmonary metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports showed that inhibition of NF-kappa B signal pathways can promote apoptosis [ 43 ]. Previously, it was shown showed that plumbagin inhibits tumor cell proliferation of gastric cancer through the NF-kappa B pathway [ 44 ]. NF-kappa B was down-regulated with CHSP treatment, showing that similar to PTEN, promotion of apoptosis and anti-proliferation in ovarian cancer cells may also be attributed to the down-regulation of NF-kappa B protein.…”
Section: Discussionmentioning
confidence: 99%
“… 9 PLB may be an effective drug in inhibiting the tumor angiogenesis of gastric cancer and the mechanism of anti-tumor may be associated with NF-κB pathway. 10 …”
Section: Introductionmentioning
confidence: 99%
“…9 PLB may be an effective drug in inhibiting the tumor angiogenesis of gastric cancer and the mechanism of anti-tumor may be associated with NF-κB pathway. 10 Tazemetostat (EPZ-6438, Figure 1A), a first-in-class small molecule enhancer of zeste homolog 2 (EZH2) inhibitor, is developed by Epizyme in collaboration with Eisai, and it is the first therapy to be approved specifically for the treatment of epithelioid sarcoma. 11 Tazemetostat was another important supplement for the treatment of patients with relapsed or refractory follicular lymphoma (R/R FL), it likely helps improve the development trajectory of the disease.…”
Section: Introductionmentioning
confidence: 99%